HRM Model In Civil-Military Environment: Investigation Of The Influencing Factors On Performance - Levianto, Jubei; Husin, Zulkifli; Kusnadi, Kusnadi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Research Aims: The objectives of this study are to analyze the factors that affect the employees' performance of the Ministry ofDefense. The analysis was performed by a reflective model with Intelligence, Stress Resistance, Personnel Relationship, Job BurnOut, and Career Strategies as independent variables; Efficacy as a mediator; and Performance as the dependent variable. Design/methodology/approach: the research was conducted by a mixed-method, which is a narrative exploration of variables throughsemi-structured interviews of five staff officials at the Ministry of Defense- Indonesia, and then the model of Structural Equation Model-Partial Least Square (SEM-PLS) was populated with 180 participants. Research Findings: Four of the six variables studied in this study have a direct impact on performance: Intelligence, Personnel Relations, Career Strategies, and Efficacy. While the effect ofStress Resistance and Fatigue on Performance is not significant, besides these four variables also have a significant indirect effectmediated by Efficacy. Theoretical Contribution/Originality: The findings provide an understanding of the variables that affect theperformance of the employees in the office populated by military and civilian personnel. Managerial Implication: The results are useful for the manager by implementing the findings into HRM policies. Research limitation & implications: The results need to be confirmed using other personality traits such as